Plato, Buber and Bourdieuan Philosophies as Templates for Academic Mentoring in Higher Education in Nigeria (2015)
Mentoring in higher education has become an integral aspect of continuing professional development in teaching and many other fields. In Nigeria, a widely accepted theory of mentoring in higher education with a philosophical basis is yet to evolve. Existing studies on mentoring scarcely justifies a sound theoretical base to underpin policy and practice for Nigeria‟s higher education. This has resulted in a preponderance of vague variables for the application and appropriation of important propositions of mentoring in higher education as can be gleaned from the National Policy on Education. This study, therefore, critically enunciated the tripartite philosophical theories of Plato, Martin Buber and Pierre Bourdieu and teased out a mentoring model with a view to providing an intellectual foundation for the institutionalisation of formal mentoring programmes for beginning academics in Nigeria. The theoretical framework of this study was gleaned from Plato‟s theory of education, Buber‟s theory of Ich und du (I-and-thou relationship) and Bourdieu‟s theory of habitus, capital, field and practice in reproduction in education, society and culture. The study employed the philosophical research methods of critical analysis, speculation, prescription, as well as the historical research method. The historical method was used as a tool for reconstructing the past; the analytic method to examine and clarify the concepts used in the study so as to avoid ambiguities and explore meanings of basic concepts. In addition, the speculative method was used to examine and establish the ideals and values of mentoring in higher education in theory and practice, while the prescriptive method was used to develop a programme of action based on the conclusions from the activities of analysis and speculation. Plato‟s one on one mentoring model provides and encourages apprenticeship for beginning academics. Buber‟s mantra provides a framework for the existence of a humane relationship amongst people, including the mentor and the mentee with a view to building a strong support system for beginning academics, while Bourdieuan engagement mentoring model supports professionalisation. The theories of Plato, Buber and Bourdieu on mentoring can address the challenges posed by the proliferation of higher education institutions, burgeoning retirement crises, attrition and so on, without a corresponding number of experts ready to take over. The rapid increase in the number of universities to 147 between November 1948 and April 2015 running over 1,450 programmes for more than 1.5 million registered students and academic staff of about 28,000, which is less than the estimated staff requirements of about 36,000, leading to a serious shortfall with consequent negative implications on the quality of programmes delivery, will be effectively checked using this philosophical tripod to institutionalise a Mentoring Action Project for Higher Education in Nigeria. Plato, Buber and Bourdieuan philosophies provided an existentialist paradigm for the institutionalisation of a one on one mentoring templates that leans on the analysis of the concepts of mentor-mentee relationship, inter-dependence, encounter, dialogue, sharing, mutuality, co-operation and fraternal love as germane recipes, located in nurturing, friendship, and apprenticeship mentoring styles.